Drug Transporters ABCB1 (P-gp) and OATP, but not Drug-Metabolizing Enzyme CYP3A4, Affect the Pharmacokinetics of the Psychoactive Alkaloid Ibogaine and its Metabolites - F. Martins, Margarida L.; Heydari, Paniz; Li, Wenlong; Martínez-Chávez, Alejandra; Venekamp, Nikkie; Lebre, Maria C.; Lucas, Luc; Beijnen, Jos H.; Schinkel, Alfred H. (Frontiers in Pharmacology, 2022)
The psychedelic alkaloid ibogaine is increasingly used as an oral treatment for substance use disorders, despite being unlicensed in most countries and having reported adverse events. Using wild-type and genetically modified mice, we investigated the impact of mouse (m)Abcb1a/1b and Abcg2 drug efflux transporters, human and mouse OATP drug uptake transporters, and the CYP3A drug-metabolizing complex on the pharmacokinetics of ibogaine and its main metabolites. Following oral ibogaine administration (10 mg/kg) to mice, we observed a rapid and extensive conversion of ibogaine to noribogaine (active metabolite) and noribogaine glucuronide. Mouse Abcb1a/1b, in combination with mAbcg2, modestly restricted the systemic exposure (plasma AUC) and peak plasma concentration (Cmax) of ibogaine. Accordingly, we found a ~2-fold decrease in the relative recovery of ibogaine in the small intestine with fecal content in the absence of both transporters compared to the wild-type situation. Ibogaine presented good intrinsic brain penetration even in wild-type mice (brain-to-plasma ratio of 3.4). However, this was further increased by 1.5-fold in Abcb1a/1b;Abcg2-/- mice, but not in Abcg2-/- mice, revealing a stronger effect of mAbcb1a/1b in restricting ibogaine brain penetration. The studied human OATP transporters showed no major impact on ibogaine plasma and tissue disposition, but the mOatp1a/1b proteins modestly affected the plasma exposure of ibogaine metabolites and the tissue disposition of noribogaine glucuronide. No considerable role of mouse Cyp3a knockout or transgenic human CYP3A4 overexpression was observed in the pharmacokinetics of ibogaine and its metabolites. In summary, ABCB1, in combination with ABCG2, limits the oral availability of ibogaine, possibly by mediating its hepatobiliary and/or direct intestinal excretion. Moreover, ABCB1 restricts ibogaine brain penetration. Variation in ABCB1/ABCG2 activity due to genetic variation and/or pharmacologic inhibition might therefore affect ibogaine exposure in patients, but only to a limited extent. The insignificant impact of human CYP3A4 and OATP1B1/1B3 transporters may be clinically advantageous for ibogaine and noribogaine use, as it decreases the risks of undesirable drug interactions or interindividual variation related to CYP3A4 and/or OATP activity.